Minimally invasive fetoscopic resection of life-threatening amniotic band constrictions in a human fetus at 22 + 2 weeks of gestation complicated by subtotal chorioamniotic separation and partial placental abruption: case report - Riehle, Nadja; Nowak, Oliver Claudius; Messroghli, Leila; Wakerlin, Samantha; Schaible, Thomas; Kohl, Thomas (Children, 2025)
Amniotic band syndrome is a constrictive phenomenon in fetal development that can provoke limb autoamputation, malformation, trunk division, and umbilical cord strangulation. The latter two complications will ultimately lead to fetal demise if left untreated. If detected early enough, select cases may benefit from prenatal resection of the amniotic bands, thus preventing amputation and fetal death. Yet, especially in the presence of complete chorioamniotic separation, these procedures are rare, technically difficult, and not without significant risk. Objectives: The purpose of this report is to present the surgical technique and outcome of a challenging percutaneous fetoscopic intervention in a human fetus with amniotic band constrictions of a fetal thigh, retroplacental hematoma, partial placental abruption, subtotal chorioamniotic separation, and multiple amniotic bands encircling the umbilical cord. Methods: Minimally invasive, fetoscopic surgery to salvage the fetal life and lower leg was performed at 22 + 2 weeks of gestation under general maternofetal anesthesia. Results: Total resection of all amniotic bands was achieved, notwithstanding the aforementioned challenges. No surgical complications were observed. Despite preterm delivery at 25 + 4 weeks of gestation, the postnatal experience for the infant was favorable and uncomplicated as it furthermore benefitted from neonatal intensive care. At almost three years of age, the child remains healthy and demonstrates normal function of the formerly constricted leg. Conclusions: Our case shows that the combination of tested percutaneous fetoscopic techniques, high-risk obstetrics, and modern neonatology can overcome multiple obstacles in order to save a fetal patient stuck in a near-hopeless situation.
Online veröffentlicht: 26. Dezember 2024
Gesehen am 05.08.2025